Study on the acoustic emission effect of plasma plume in pulsed laser welding. (1st June 2019) - Luo, Yi; Zhu, Liang; Han, Jingtao; Xie, Xiaojian; Wan, Rui; Zhu, Yang
Highlights: The source mechanism for AE generation is the recoil force and thermal vibration. The AE signals contain valuable information about plasma plume. AE signals shows the energy characteristics of plasma plume. AE signals are valuable to evaluate the plasma plume and the weld penetration. Abstract: The acoustic emission (AE) signals were detected in real-time during the process of pulsed YAG laser welding. Some characteristic analysis methods, including AE count statistic, root mean square (RMS) waveform calculation and power spectrum distribution, were used to analyze the AE signals. According to the AE signals, the characteristics of plasma plume and penetration of weld bead were studied. The results showed that the source mechanism for AE generation was the recoil force and thermal vibration generated by the plasma plume acting on molten pool. The AE signals detected in welding contained a lot of valuable information about plasma plume. AE count, RMS waveform and power spectrum of AE signals showed the energy characteristics of plasma plume in time and frequency domain. Therefore, AE signals detected in pulsed laser welding had clear correlations with plasma plume, which were valuable to evaluate the plasma plume and the penetration of weld bead.